Retrospective analysis of iatrogenic diseases in cattle requiring admission to a veterinary hospital. Issue 1 (18th February 2019) - Sala, Giulia; Boccardo, Antonio; Fantinato, Eleonora; Coppoletta, Eleonora; Bronzo, Valerio; Riccaboni, Pietro; Belloli, Angelo Giovanni; Pravettoni, Davide
Abstract : Iatrogenic diseases in veterinary medicine are often related to malpractice or lack of skill. For this retrospective study, 4262 clinical records of cattle admitted to the veterinary teaching hospital of the University of Milan between 2005 and 2017 were analysed, and 121 cases (2.8 per cent), referred for an iatrogenic‐related disease, were selected. The findings showed that iatrogenic diseases were more often caused by farmers (92.6per cent) than by bovine practitioners (7.4 per cent). Iatrogenic diseases were caused mainly by the improper administration of drugs (43.0 per cent), forced extraction during calving (19.8 per cent), forced milk or colostrum feeding, which was often performed by awkward administration using a nipple bottle (14.9 per cent) or by oral oesophageal tubing (15.7 per cent). Moreover, farmers often performed medical, nursing and zootechnical procedures without adequate training. The role of the practitioner is fundamental in farmer education. Clinicians, especially in some professional branches such as neonatology, should not delegate medical procedures to untrained farmers. Effective tutoring and good communication with farmers play a key role in dairy herd health and consequently in public health. This then can lead to a decrease in improper drug administration, the prevention of antibiotic resistance and the reduction of treatment costs.